Evaluating nonlinear distortion of single and dual channel excitation of an amplifier at 24 GHz. Issue 9 (22nd May 2021) - Panigrahi, Smruti Ranjan; Rönnow, Daniel
Abstract: Experimental characterization of an amplifier's nonlinear properties at 24 GHz is presented in single and dual‐band operation using orthogonal frequency‐division multiplex signals. A test system for characterizing an amplifier's nonlinear properties at millimeter‐wave frequencies for single and dual‐band excitation is presented. The use of standard instrument enables a feasible test system. Analytical expressions based on a statistical analysis of signals and hardware impairments were used to analyze the experimental data versus power level and found to describe well the experimental results, including inter‐ and cross‐modulation distortion. Parameters are derived that could be used in system studies.